Fontan Completion in Adult Patients with Functionally Univentricular Hearts - Alpat, Safak; Aydin, Ahmet; Aykan, Hakan; Yilmaz, Mustafa (The Thoracic and Cardiovascular Surgeon, 2024)
Background Although there are considerable amounts of data on the outcomes of pediatric patients who have undergone Fontan repair, little is known about having Fontan completed in adulthood. The study presented the midterm results of our unit's experience with the Fontan completion procedure in adult patients with functionally univentricular hearts.Methods Between 2014 and 2023, 16 adult patients underwent total cavopulmonary connection (TCPC) completion. Relevant information was retrospectively collected.Results Sixteen patients with a median age of 19 years (18–21 years) were included. Median arterial oxygen saturation was 76% (70–80.75%), and 62.5% of the patients were New York Heart Association (NYHA) Class III. The median mean pulmonary artery pressure was 14 mm Hg (9.5–14.5 mm Hg). Nine patients (56%) had heterotaxy syndrome, and the median time between the last operation and TCPC was 15.5 years (6.75–17.5 years). The median durations for bypass and cross-clamp were 160 minutes (130–201 minutes) and 120 minutes (84.5–137.5 minutes), consecutively. The postoperative course was straightforward in all. The median arterial oxygen saturation before discharge was 89.5% (85–90%), and 68.75% of the patients were NYHA Class II. Follow-up was complete for all patients with a median of 24 months. There was no early or late mortality or significant morbidity during the study period.Conclusion We concluded that the intra-extracardiac Fontan technique was feasible for meticulously selected adults undergoing TCPC completion, as evidenced by an acceptable mortality rate and a satisfactory midterm outcome, including improvements in their NYHA functional class. However, the long-term consequences must be monitored.
Keywords: Adult congenital; Fontan; total cavopulmonary connection; single ventricle